VD_FINDINFO HC / 2011 / 211 vom 12. April 2011 - VD Tribunal cantonal (2011)
EXPULSION DE LOCATAIRE, EXÉCUTION FORCÉE | 138 al. 3 let. a CPC (CH), 309 let. a CPC (CH), 319 let. a CPC (CH), 320 CPC (CH), 320 let. a CPC (CH), 320 let. b CPC (CH), 326 al. 1 CPC (CH), 326 CPC (CH), 341 CPC (CH), 405 al. 1 CPC (CH)